Study on the Influence of Axis Parallelism Error on Tooth Root Deformation Bending Stress - Yang Zhou; Jipeng Li; Guangwei Yang (Jixie chuandong)
In order to study the influence of assembly parallelism error caused by the axis tilt on the tooth root bending deformation， a set of gearbox test platform with adjustable gear axis and a complete strain acquisition and analysis system are designed and test verification is carried out. Based on the allowable deflection of the inner and outer rings of the spherical roller bearing， a finite element model of gear contact with different degrees of axis offset is established， and dynamic simulation analysis is performed to obtain the tooth root strain and stress distribution curve during the meshing process. Through the design of different adjustment methods of different axes， the actual and theoretical values of the angular deviation of the two axes before and after adjustment are compared to verify the feasibility of the adjustment device. Finally， the tooth root strain of different axis parallel error are tested through a strain acquisition system composed of a strain gauge acquisition card， the corresponding strain and stress distribution curve is obtained， and compared with the simulation strain and stress curve， the influence of the axis parallel error on the bending deformation at the dangerous root cross section is obtained.